Magnetic and thermal transport properties of SrFe12O19 permanent magnets with anisotropic grain structure. (5th July 2017) - Volodchenkov, A.D.; Ramirez, S.; Samnakay, R.; Salgado, R.; Kodera, Y.; Balandin, A.A.; Garay, J.E.
Abstract: Permanent magnets are gaining increasing interest and importance for applications such as generators and motors. Thermal management is a key concern since performance of magnets decreases with temperature. We investigate the magnetic and thermal transport properties of rare earth-free, fine-grained SrFe12 O19 magnets produced by the current activated pressure assisted densification. We propose a cooling scheme based on an anisotropic grain structure that can help retain magnetic performance under high temperature conditions. The synthesized magnets have aligned grains such that their magnetic easy axis is perpendicular to their largest surface area to maximize their magnetic performance. The SrFe12 O19 magnets have fine grain sizes in the cross-plane direction and substantially larger grain sizes in the in-plane direction. This microstructure results in approximately a factor of two higher thermal conductivity in the in-plane direction, providing an opportunity for effective cooling. The phonons are the dominant heat carriers near room temperature. Temperature and direction dependent thermal conductivity measurements indicate that both Umklapp and grain boundary scattering are important in the in-plane direction, while grain boundary scattering dominates the cross-plane thermal transport. The proposed design strategy should translate well to other material systems and has important implications for thermal management of nanostructured permanent magnets. Graphical abstract: The nano/microstructural design strategy for permanent magnets allows for maximizing magnetic properties, while providing a high thermal conductivity ( k ) direction for efficient cooling. Highlights: We introduce a nano/microstructural design strategy for thermal management of permanent magnets The magnets have aligned grains for magnetic performance and increasing thermal conductivity for effective cooling The strategy will translate well to other magnetic materials for energy efficient applications such as generators and motors